O PROCESSO DE MUDANÇA EM UMA INSTITUIÇÃO PÚBLICA SOBRE A ÓTICA DAS CAPACIDADES DINÂMICAS - Adriela de Marchi (Universidade Federal de Santa Catarina, 2018)
Public sector managers are increasingly used management strategies to improve organizational performance (LLEWELLYN; TAPPIN, 2003). As the main purpose of the public authorities is the continuous improvement of service delivery in order to better serve users, the dynamic capabilities come against as a potentially valuable strategic approach in the public sector (PABLO et al., 2007). This article aims to analyze the dynamic capabilities in a federal university, using the model proposed by Wang and Ahmed (2007). To this end, we used secondary data available on the institution by means of a longitudinal study with content analysis of the period of management reporting site 2005 to 2013. The results of the document analysis show that actions addressed the management reports are related the innovative dimensions, absorptive and adaptive constituting the dynamic capacity as the institution strives for excellence in public education, scientific production and contribution to social development, seeking trained servers, valued and committed to the mission; adequate infrastructure; effective management supported by information from administrative, academic and technical processes.